The Sonia Case: An Illustration of the Use of the M/81 Technique - Mullet, E.; Chami, M.; Francequin-Chartier, G.; Munoz-Sastré, M. T.; Neto, F.; Rieu-Fichot, C. (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper illustrates a technique designed to help adolescents and young adults of: (a) the relationships between certain classic determinants e.g. (prestige, salary, career prospects) and their vocational preference system; (b) the strong and weak points in their information systems; and, (c) the internal structure of their occupational representations. An example of extension to the family is presented and analyzed.